Class III / short line system inventory to determine 286,000 lb (129,844 kg) railcar operational status in Kansas and determination of ballast fouling using ground penetrating radar - Shofstall, Lisa (Kansas State University, 2017)
The rail industry's recent shift towards larger and heavier railcars has influenced Class III / short line railroad operation and track maintenance costs. Class III railroads earn less than $38.1 million in in annual revenue and generally operate first and last leg shipping for their customers. In Kansas, Class III railroads operate approximately 40 percent of the roughly 2,800 miles (4,500 km) of rail; however, due to the current Class III track condition they move lighter railcars at lower speeds than Class I railroads. The State of Kansas statutorily allots $5 million to support rail improvement projects, primarily for Class III railroads. Therefore, the objective of this study was to conduct an inventory of Kansas’s Class III rail network to identify the track segments in need of this support that would be most beneficial to the rail system. Representatives of each railroad were contacted and received a survey requesting information regarding the operational and structural status of their systems. The data collected were organized and processed to determine the sections of track that can accommodate the heavier axle load cars that are currently being utilized by Class I railroads. This study identified that Class III railroads shipped over 155,000 carloads of freight in 2016 and 30 percent of Kansas’s Class III track can currently accommodate heavy axle cars. The increased load from the increased railcar size has also increased the risk of damage to railroad’s track structure. Railroad ballast is the free draining granular material that supports the track structure. As the track ages, small particles can fill the voids of the granular material which is a process known as fouling. Established methods for determining the fouling of a section of ballast are destructive tests that usually require the railroad to restrict or reroute traffic on its network. Ground Penetrating Radar (GPR) is a nondestructive geophysical surveying method that measures the time required for electromagnetic wave impulses to reflect off differing subsurface interfaces. Historically, GPR surveys of track structures primarily determine the depth of ballast and track geometry. The objective of this study was to determine the viability of utilizing the laboratory’s existing GPR equipment to develop a methodology of measuring ballast fouling nondestructively. A 48 x 48 x 48 in (1.2 x 1.2 x 1.2 m) test box was built. The test box was filled with 48 in (1.2 m) of clean and ballast. Tests were run on dry and partially saturated material, wetted using 6 gallons (22.7 L). GPR data were collected hourly for the first 6 hours, then at the multiples of 12 and 24 hour marks for one week. Sand was chosen as an absorbent geologic material for the second stage of testing since no fouled ballast could be acquired at the time of the study. A 27 x18 x 18 in (0.69 x 0.46 x 0.046 m) box was filled with sand and wetted with water in one gallon (7.5 L) increments. GPR scans and samples to determine the water content were collected after the addition of each gallon. The data collected were processed to determine soil properties. Preliminary results from this research indicate that the GPR set up utilized can effectively determine the dielectric constant of geologic materials including ballast, although the dielectric constant is highly dependent on the volumetric moisture content of the material.
Keywords: Kansas; Short line; Class III; GPR; Ground penetrating radar; BallastRailroad